Changes in Consumer Behavior Through Digital Transaction Counseling at the Student Cooperative (KOPMA) - Haholongan, Rutinaias; Anwar, Fajri Nurul; Mumtaz, Zufar Hafiz Islamazfar; Aisyah, Siti; Maharani, Fadillah; Wulandari, Putri (Entrepreneurship and Community Development, 2024)
This research aims to determine changes in consumer behavior through digital transaction counseling at Student Cooperatives (KOPMA). The method used in this research was observation, by providing counseling to 22 Kopma members on the STEI Indonesia campus in Jakarta. The research results show that the use of digital transactions can have a positive impact on consumer behavior. Students who want to make transactions in cooperatives will find it easier and more affordable with the use of digital transactions. The conclusion of this research is the importance of knowing the latest developments related to technology today, especially for daily needs such as easier payment transactions.